Influence of the Turkish Empire on Malaya in the Malay Manuscript of the Leiden University Library Collection - Muhammad, S.J.N; Rahman, N.S.A; NRNM Affendi; Asmiaty Amat (Psychology and Education, 2021)
When researching the catalogues about Malay manuscripts at the library of Leiden University, Netherlands, there was a list of records about Turkey and Malaya’s relations in various manuscript collections in the library. This is important to be highlight to see how far the two empires’ relationship are in Malay manuscripts. Thus, this writing will analyze the Turkish Empire’s influence towards the Malay government in various aspects. The analyze will using the selected Malay manuscripts through the Leiden University Library collection. Qualitative content analysis methods will use to examine the topics. The expectation of writing shows that there are significant influences towards the Malay government, especially about lineage and politics. This writing will directly contribute to the studies on international relations between the Turkish Empire and Malay government and highlight the way the government practiced by the Islamic government in maintaining the relationship as stated in the Malay manuscript.